Agnis

answers: 1

Register to add an answer

Answer:

6x-5y =-4

6x=5y-4

x=(5y-4)/6 ------ I

9x +3y =11

9(5y-4)/6 + 3y =11. from I

45y/6 -36/6 +3y =11

45y/6 +3y =11 +36/6

(45y+18y)/6= 11+6

63y = 17*6

y=102/63

putting value of y

6x-5y =-4

6x- 5*102/63=-4

6x=510/63-4

6x=510-4*63 / 63

6x = 510-252 /63

x = 258 / 63*6

x=43/63

39

Wally

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions